RANCANGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS MICROSOFT ACCES BERDASARKAN SAK EMKM PADA UKM DEWI PROL TAPE - Admaja, Fitroh Marga Mila Aria; Oktaviana, Ulfi Kartika (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Dewi Prol Tape is one of Micro Small and Medium Entities which already have Micro Small Business Permit (IUMK) and turnover which increase every year. With administrative completeness as well as a good turnover increase, in the preparation of its financial statements are still not compiled well and in accordance with SAK EMKM. The preparation of the required financial statements is software-based for easy use by the UKM. Software used is microsoft acces where in operation does not require high accounting skills and does not require the cost to get it.So with that background this research is done with the title: "Design of Preparation of Financial Statements Based in Microsoft Access Based on Financial Accounting Standards of Small and Medium Entities (SAK EMKM) at UKM Dewi Prol Tape".This research used qualitative method with case study approach. The location of the research is UKM Dewi Prol Tape located on Danau Paniai street 2 c7 e5 Sawojajar, Madyopuro, Kedungkandang, Malang City. The subject of research is the owner of UKM Dewi Prol Tape. The data was collected by triangulation method. Data analysis methods that used consist of: data collection, data reduction, data presentation and conclusion.The result of the research shows that the design of preparation of financial statements based in Microsoft access based on Financial Accounting Standards of Small and Medium Entities (SAK EMKM) for UKM Dewi Prol Tape is: report of cost of goods manufactured, income statement, statement of financial position and notes to financial statement. And the obstacles that faced in the presentation of financial statements are: a) lack of human resources in preparing financial statements, b) lack of knowledge of Financial Accounting Standards of Small and Medium Entities (SAK EMKM).